2012
DOI: 10.23986/afsci.6082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic acid on the meat quality properties and the taste of pork Serratus ventralis muscle

Abstract: In this work was evaluated the effect of lactic acid treatment method in pork Serratus ventralis muscle on meat quality parameters pH, color, weight loss, cooking loss, hardness, and taste. The treatment was performed by immersing the sample in lactic acid solutions at two concentrations (1 and 3% v v -1 ) for 1 and 3 min., immediately the samples were stored at 4 °C during 7 days. The taste was evaluated employing trained and untrained judges. Only hardness, weight loss and cooking loss, were affected by lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
3
17
0
1
Order By: Relevance
“…In agreement with our results, Grajales‐Lagunes et al () observed a reduction on pH values of pork ( Serratus ventralis ) treated with LA solutions (1–3%) immediately after application, as a result of acid concentration, although no difference on pH values were observed from 7 days of storage when compared to control samples. In addition, Naveena, Muthukumar, Sen, Babji, and Murthy () observed a pH reduction of buffalo steaks treated with 2% of LA solutions in the first 6 days of storage, followed by a pH increase, corroborating in part with our results.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, Grajales‐Lagunes et al () observed a reduction on pH values of pork ( Serratus ventralis ) treated with LA solutions (1–3%) immediately after application, as a result of acid concentration, although no difference on pH values were observed from 7 days of storage when compared to control samples. In addition, Naveena, Muthukumar, Sen, Babji, and Murthy () observed a pH reduction of buffalo steaks treated with 2% of LA solutions in the first 6 days of storage, followed by a pH increase, corroborating in part with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The slight increases in pH during refrigerated storage in meat samples containing OL could be explained by an effect of OL on the buffering capacity of meat at certain pH values . OL might also promoter proteolysis in meat.…”
Section: Resultsmentioning
confidence: 99%
“…The first group (A) is for control and without garlic extract. The other groups (B, C, D, and E) were immersed to garlic extract solutions at (prepared using distilled water) 0.5, 1, 1.5, and 2%, respectively, for 1 min appropriate to literature then all groups were vacuum‐packaged with in aseptic conditions (Barmpalia et al, ; Carlos & Harrison, ; Grajales‐Lagunes, Rivera‐Bautista, Ruiz‐Cabrer, Gonzales‐Garcia, & Ramirez‐Telles, ). Finally, they stored in 4°C refrigerator for microbiological analysis.…”
Section: Methodsmentioning
confidence: 99%